Goyangi means cat - McDonnell, Christine; Johnson, Steve, 1960-; Fancher, Lou (New York : Viking, 2011)
An understanding cat helps a young Korean girl adjust to her new home in America.
Keywords: Home -- Juvenile fiction; Korean Americans -- Juvenile fiction; Intercountry adoption -- Juvenile fiction; Adoption -- Juvenile fiction; Cats -- Juvenile fiction; Home -- Fiction; Korean Americans -- Fiction; Intercountry adoption -- Fiction; Adoption -- Fiction; Cats -- Fiction